The concept of cultural ecosystem services in urban areas (Geography and Tourism, 2018)
The article presents major issues related to the development of cultural ecosystem services in urban areas. Major advantages related to urban development in the context of making the concept for development of such services effective are shown. The authors start with the overall characteristics of ecosystem services. Then by analyzing the cultural aspect of ecosystem services and their impact on human well-being, the authors narrow the phenomenon. Further in the article, they focus on presenting the importance of „green space”, while making a reference to cultural ecosystem services.